2001
DOI: 10.1083/jcb.200101057
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for FGF and extracellular signal–regulated kinase in gap junction–mediated intercellular communication in the lens

Abstract: Gap junction–mediated intercellular coupling is higher in the equatorial region of the lens than at either pole, a property believed to be essential for lens transparency. We show that fibroblast growth factor (FGF) upregulates gap junctional intercellular dye transfer in primary cultures of embryonic chick lens cells without detectably increasing either gap junction protein (connexin) synthesis or assembly. Insulin and insulin-like growth factor 1, as potent as FGF in inducing lens cell differentiation, had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 93 publications
2
116
0
1
Order By: Relevance
“…Scrape-loading and dye transfer assay for gap junction intercellular communication. BxPC-3 cells were assessed for gap junction-mediated intercellular communication using a protocol adapted from that of Le and Musil (27,28). Cells were plated on glass coverslips in 35-mm-diameter dishes (6 ϫ 10 5 cells/ dish) and grown for 4 days to confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Scrape-loading and dye transfer assay for gap junction intercellular communication. BxPC-3 cells were assessed for gap junction-mediated intercellular communication using a protocol adapted from that of Le and Musil (27,28). Cells were plated on glass coverslips in 35-mm-diameter dishes (6 ϫ 10 5 cells/ dish) and grown for 4 days to confluence.…”
Section: Methodsmentioning
confidence: 99%
“…In chick lens cultures, FGF controls the opening status of gap junctions (GJs) and enhances GJC (Le and Musil, 2001). In chick limb bud cultures, application of FGF4/8 augments expression of the GJ gene connexin 43 (Cx43; Makarenkova et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that connexin diversity plays an integral role in the correct development and function of the mammalian lens, contributing to changes in channel gating and permeation (Gao et al, 2004;Le and Musil, 2001;MartinezWittinghan et al, 2003;Rong et al, 2002;White, 2003). In the past, different Cx50 variants have been described in the development of several distinct types of dominant cataract in mice (Chang et al, 2002;Graw et al, 2001;Steele et al, 1998;Xia et al, 2006a).…”
Section: Journal Of Cell Science 120 (23)mentioning
confidence: 99%